2015
DOI: 10.1371/journal.pone.0116808
|View full text |Cite
|
Sign up to set email alerts
|

Co-Detection of Virulent Escherichia coli Genes in Surface Water Sources

Abstract: McNemar’s test and the Pearson Chi-square were used to assess the co-detection and observed frequency, respectively, for potentially virulent E. coli genes in river water. Conventional multiplex Polymerase Chain Reaction (PCR) assays confirmed the presence of the aggR gene (69%), ipaH gene (23%) and the stx gene (15%) carried by Enteroaggregative E. coli (EAEC), Enteroinvasive E. coli (EIEC) and Enterohermorrhagic E. coli (EHEC), respectively, in river water samples collected from the Berg River (Paarl, South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
3
15
3
1
Order By: Relevance
“…In this study low frequency of STEC and EIEC (one infections was found We can hypothesize that our strains (diarrheal stool samples) analysedwere not related olitis and haemolytic uremic syndrome. Similar results were found in subSaharan Africa and others countries [2,26,27,28]. ETEC causes a significant number of cases of childhooddiarrhoea and gastroenteritis among the most common agent of traveller'sdiarrhoea with food and water implicated as the modes of transmission [3].…”
Section: Discussionsupporting
confidence: 79%
“…In this study low frequency of STEC and EIEC (one infections was found We can hypothesize that our strains (diarrheal stool samples) analysedwere not related olitis and haemolytic uremic syndrome. Similar results were found in subSaharan Africa and others countries [2,26,27,28]. ETEC causes a significant number of cases of childhooddiarrhoea and gastroenteritis among the most common agent of traveller'sdiarrhoea with food and water implicated as the modes of transmission [3].…”
Section: Discussionsupporting
confidence: 79%
“…PCR of the uldA gene was performed to confirm E. coli at the genus level (10). PCR was performed on the pCVD432 gene for EAEC (11), eae gene for EPEC (12), elt, est genes for ETEC (13), ial gene for EIEC (4), and stx gene for EHEC (12). The ESBL genes (bla TEM , bla CTX−M−1, 2, 8, 14, 15 , and bla SHV ) and…”
Section: Genotypic Identificationmentioning
confidence: 99%
“…In order to extract total genomic DNA from the tank water samples (950 mL) a modified version of the boiling method was utilized (Watterworth et al, 2005) as outlined in Ndlovu et al (2015). Once DNA extractions had been performed, genomic DNA and total DNA was visualized on a 0.8% agarose gel stained with 0.5 μg/mL ethidium bromide.…”
Section: Extraction Of Total Dna From Tank Water Samplesmentioning
confidence: 99%